The zooplankton food web under East Antarctic pack ice - a stable isotope study - Jia, Z; Swadling, KM; Meiners, KM; Kawaguchi, S; Virtue, P (Deep Sea Research Part II: Topical Studies in Oceanography, 2016)
Understanding how sea ice serves zooplankton species during the food-limited season is crucial information to evaluate the potential responses of pelagic food webs to changes in sea-ice conditions in the Southern Ocean. Stable isotope analyses ( 13 C/ 12 C and 15 N/ 14 N) were used to compare the dietary preferences and trophic relationships of major zooplankton species under pack ice during two winterspring transitions (2007 and 2012). During sampling, furcilia of Euphausia superba demonstrated dietary plasticity between years, herbivory when feeding on sea-ice biota, and with a more heterotrophic diet when feeding from both the sea ice and the water column. Carbon isotope signatures suggested that the pteropod Limacina helicina , small copepods Oithona spp., ostracods and amphipods relied heavily on sea-ice biota. Post larval E. superba and omnivorous krill Thysanoessa macrura consumed both water column and ice biota, but further investigations are needed to estimate the contribution from each source. Large copepods and chaetognaths overwintered on a water column-based diet. Our study suggests that warm and permeable sea ice is more likely to provide food for zooplankton species under the ice than the colder ice.